PERGESERAN GAYA HIDUP PEREMPUAN KOTA: STUDI KASUS KONSUMSI “FASHION” DI INDONESIA - Ratih Baiduri (Universitas Negeri Medan, 2013)
ABSTRACT This paper discusses the phenomenon of a shift in women's lifestyle fashion consumption in Indonesia. In this paper fashion could be interpreted as clothing, fashion, makeup, and style. The dynamics of changes in social and cultural life experienced by urban women in Indonesia have caused a shift in lifestyle in terms of fashion consumption. This shift was indicated in the function and meaning of fashion itself, namely in: (1) positioning the production of desire, identity / ethnic identity / group; (2) position the power of individuals / groups; (3) shows the ideology / ideological resistance and (4 ) to identify the context of sex / gender. The factors that case it are factors coming from within the individual (internal) and factors originating from outside the individual (external). The internal factors include the attitudes, experiences and observations, personality, self-concept, motives and perceptions. While the external factors are included in reference group, family, social class, and culture. The shift in the consumption of fashion lifestyle is adopted in every aspect of cultural life of urban women in Indonesia showed that there was a shift from the direction of homogenization (uniformity) in the direction heterogeneous (differentiation) in terms of fashion consumption. Kata Kunci : Pergeseran gaya hidup, perempuan, konsumsi fashion.